Development of a Leader Tool for Assessing and Mitigating Suicide Risk Factors. (19th February 2020) - Hoyt, Tim; Repke, Diana; Barry, David; Baisley, Margaret; Jervis, Shellie; Black, Ryan; McCreight, Sarah; Prendergast, Daniel; Brinton, Chauncy; Amin, Rohul
ABSTRACT: Introduction: Despite efforts in prevention, suicide rates in the US military remain unchanged. This article describes the development of a tool for leaders to identify and mitigate suicide risk factors. Methods: A seven-item measure, the Leader Suicide Risk Assessment Tool (LSRAT), was constructed to allow leaders to assess and mitigate suicide drivers. During a 6-mo pilot, unit leaders completed the LSRAT for 161 at-risk soldiers. The LSRAT data were compared to clinical data from a subset of these soldiers. Results: The LSRAT showed good test-retest reliability. The LSRAT scores showed significant correlations with both clinical and screening measures of suicidality. Command actions mitigated or partially mitigated 89% of risk factors identified on the LSRAT. Conclusions: This study provides initial psychometric data on a tool that prescribes concrete responses to mitigate risk. The LSRAT may be a valid and feasible tool to assist front-line commanders in identifying potential area's risk mitigation. Synchronization efforts between commanders, clinicians, and support services are crucial to ensure effective intervention to prevent suicide behavior.